Essential Features for Mobile Applications to Assist Early Childhood Educators - Boude, Oscar; Vargas Sanchez, Ana; Choconta, Johanna (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The integration of early childhood applications is increasingly common. However, in this process, educators often use academic apps from Apple and Android stores, believing they will enhance children’s training. However, most of these apps, not designed by preschool educators, fail to enhance the training processes in early childhood education. This paper aims to identify the essential features those mobile applications must possess to enhance childhood education processes. To achieve this, we conducted a qualitative study with a descriptive scope and involved teachers of childhood education from the Universidad de La Sabana in the development of the mobile application. It is also based on the Mobile-D agile development methodology. The results have enabled the development of an intuitive mobile application for early childhood children, which strengthens children’s development of cognitive, body, communicative, and aesthetic dimensions and identifies the essential elements that mobile applications should have in early childhood. The findings indicate that it is critical to involve early childhood education teachers in the development of mobile applications and that mobile applications must strike a balance between entertainment and educational content, as well as strengthen cognitive processes rather than disciplinary content.